Density by moduli and statistical convergence - Aizpuru, A.; Listán-García, M.C.; Rambla-Barreno, F. (Quaestiones mathematicae, 2014)
By using modulus functions we introduce a new concept of density for sets of natural numbers. Consequently, we obtain a generalization of the notion of statistical convergence which is studied and characterized. As an application, we prove that the ordinary convergence is equivalent to the module statistical conver- gence for every unbounded modulus function.